Low-profile dual mini-fragment plating of diaphyseal clavicle fractures. A biomechanical comparative analysis. (1st June 2022) - Pastor, T; Knobe, M; van de Wall, B J M; Rompen, I F; Zderic, I; Visscher, L; Link, B-C; Babst, R; Gueorguiev, B; Beeres, F J P
Abstract: Objective: Implant removal rates after clavicle plating are high. Recently, low-proﬁle dual mini-fragment plate constructs have proven safe for the ﬁxation of diaphyseal clavicle fractures. Therefore, the aims of this study was to investigate: (1) the biomechanical competence of different dual plate designs in terms of stiffness and cycles to failure, and (2) to compare them against 3.5 mm single superoanterior plating. Methods: 12 artificial clavicles were assigned to 2 groups and instrumented with titanium matrix mandible plates as follows: group 1 (2.5 mm anterior+2.0 mm superior) and group 2 (2.0 mm anterior+2.0 mm superior). An unstable clavicle shaft fracture (AO/OTA15.2C) was simulated. Specimens were cyclically tested to failure under craniocaudal cantilever bending, superimposed with torsion around the shaft axis and compared to previous published data of 6 locked superoanterior plates tested under the same conditions (group 3) Results: Displacement (mm) after 5000 cycles was highest in group 3 (10.7±0.8) followed by group 2 (8.5±1.0) and group 1 (7.5±1.0), respectively. Both outcomes were significantly higher in group 3 as compared to both groups 1 and 2 (p≤0.027). Cycles to failure were highest in group 3 (19536±3586) followed by group 1 (15834±3492) and group 2 (11104±3177), being significantly higher in group 3 as compared to group 2 (p=0.004). Conclusion: Low-profile 2.0/2.0 dual plates demonstrated similar initial stiffness compared to 3.5 mm single plates, however, they revealed significantly lower endurance to failure. Moreover, low-profile 2.5/2.0 dual plates showed significant higher initial stiffness and similar resistance to failure compared to 3.5 mm single locked plates and can therefore be considered as a useful alternative for diaphyseal clavicle fracture fixation. These results complement the promising results of several clinical studies.